Comparing self‐directed methods for training staff to create graphs using Graphpad Prism. Issue 1 (1st November 2018) - Berkman, Sydney J.; Roscoe, Eileen M.; Bourret, Jason C.
Abstract : An important skill for behavior analysts is creating graphs that clearly convey outcomes and conform to publication conventions. GraphPad Prism is software designed for creating scientific graphs, but no prior research has empirically evaluated training graphing skills using Prism. Two effective training methods are enhanced written instructions (EWI) and video modeling with voiceover instructions (VMVO), but no single‐subject studies have compared the effects of these methods. In this study, we compared the efficacy and social validity of EWI and VMVO for training staff to create graphs using Prism. A single‐subject design was employed to compare the effects of the methods on the individual performance of 11 graduate students. EWI and VMVO were both found to be effective, and more participants chose to use EWI.